PENGARUH PELAKSANAAN PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN PASIEN TENTANG MANAJEMEN NYERI DI RUANGAN RAWAT INAP BEDAH RSUD M. NATSIR SOLOKTAHUN 2021 - Centia Komala Sari; Annisa Sonia (Ensiklopedia of Journal, 2022)
Pain management is an action taken to reduce the pain and pain that is felt. Whether it's physiological pain or pain caused by an insertion or healing process. Based on the data that the researchers obtained at Solok Hospital on June 6 2021, it was found that out of 10 inpatient rooms at Solok Hospital, the highest number of patients experiencing pain complaints were in the surgical, obstetrics and ENT inpatient rooms. In the surgical inpatient room, the number of patients treated from January to May was 225 people with an average number of patients per month of 45 people.       Researchers have conducted research on the effect of health education on patient knowledge about pain management. This research was conducted in the surgical inpatient room of Solok Hospital on 27 October - 5 November 2021. This research was conducted because based on an initial survey, in general, patients did not know how to deal with pain that arises independently (nonpharmacological). The population in this study were 225 patients in the surgical inpatient room of Solok Hospital, with a planned sample size of 16 people. The independent variable in this study is health education and the dependent variable in this study is knowledge. This type of research is one group pretest posttest with the sampling technique using accidental sampling. The data that the researchers obtained would then be processed using the t test and analyzed using univariate and bivariate analysis.               The results showed that the average difference in knowledge about pain management before and after being given health education was -3.625 and the standard deviation was 1.31. The results of the t-test statistical test obtained a value of p = 0.000 meaning that at α = <0.05, it can be seen that there is an effect of health education on patient knowledge about pain management in the operating room of M.NatsirSolok Hospital in 2021.               For health workers, it is hoped that the head of the room in the surgical inpatient room of M.NatsirSolok Hospital will motivate the implementing nurses to provide health guidance and counseling, especially for patients who experience pain with non-pharmacological actions such as relaxation techniques, guided motivation, distraction and so that others can help. patient to prevent further pain.Keywords: Knowledge, Pain Management